Manajemen Kepemimpinan Deborah - Reviona Passa; Stevanus Adrian; Listiani Agustin; Jelita; Sarmauli (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the legitimacy of Deborah's leadership, explained within the theological and socio-cultural context of patriarchal Israel, and to determine whether Deborah's leadership pragmatism can be applied as a theological and practical solution to address contemporary issues concerning Christian women's leadership in various modern organizations. This study employed a qualitative approach with a literature review. The data used in this study were secondary. The analysis revealed that Deborah's leadership management model was proven to be transformative, strategic, and effective. The legitimacy of her leadership stems from her divine calling as a prophetess and judge, which theologically transcends the socio-cultural challenges of patriarchy. Her key managerial characteristics include steadfast faith, courage in decision-making, and strategic direction. Deborah successfully implemented synergistic management by transforming Barak's doubts into obedience through her presence and total support. Pragmatically, Deborah's leadership is the antithesis of gender discrimination. Her effectiveness in leading the nation to victory is biblical evidence that the pursuit of women's leadership qualities need not be discussed but rather recognized and developed within the context of the church and contemporary society.